2022
DOI: 10.12659/msm.936384
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sleep Duration and Sleep Disorder Data from the National Health and Nutrition Examination Survey and Stroke Among Adults in the United States

Abstract: Background We aimed to explore the association between sleep duration and sleep disorder variables obtained from the National Health and Nutrition Examination Survey (NHANES) and stroke. Material/Methods This cross-sectional study enrolled 10 442 participants from the United States. The outcome variable was stroke diagnosed by a doctor. Sleep disorder variables were assessed via self-report questionnaires and included sleep duration, the time required to fall asleep, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Stroke patients are prone to sleep disorders and may relapse several years after stroke (Jönsson et al, 2006 ). One research found that participants who slept for <6 h had a 0.97 times increased risk of stroke compared to those who slept for 6–7 h and participants with sleep disorders had 0.71 times the risk of stroke compared with those without sleep disorders (Wang and Ren, 2022 ). Our study found that people with a history of stroke and who were assessed to be at high risk of stroke had lower sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke patients are prone to sleep disorders and may relapse several years after stroke (Jönsson et al, 2006 ). One research found that participants who slept for <6 h had a 0.97 times increased risk of stroke compared to those who slept for 6–7 h and participants with sleep disorders had 0.71 times the risk of stroke compared with those without sleep disorders (Wang and Ren, 2022 ). Our study found that people with a history of stroke and who were assessed to be at high risk of stroke had lower sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is critical to a person's physical and mental health [1][2][3][4][5][6]. However, the prevalence of diagnosed sleep disorders among American patients has significantly increased over the past decade [1,5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is critical to a person's physical and mental health [1][2][3][4][5][6]. However, the prevalence of diagnosed sleep disorders among American patients has significantly increased over the past decade [1,5,[7][8][9][10]. Sleep disorders are a broad categorization of disorders that encompass conditions that lead to difficulty falling asleep, poor sleep quality, early waking, circadian rhythm disorders, parasomnias, sleep-related movement disorders, and sleep-related breathing disorders [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation